Variable Schwa Deletion in French of Orléans: The Role of Age as a Sociolinguistic Factor: A CORPUS STUDY - Belhoum, Sonia; Abdelkader Lotfi , Benhattab (JOURNAL OF ADVANCES IN LINGUISTICS, 2022)
The present paper is a micro diachronic and a socio-comparative study which examines the behaviour of a well-known pronunciation variant in French, the so-called schwa. The aim of it is to understand the nature of this variation (elision and maintenance) in monosyllabic words; clitics (#c(ə)#c) in French of Orléans, considering age as a sociolinguistic factor leading to this simplification process. Also, the evolution of the variational behaviour of this vowel in the same context across a diachronic interval of forty years (from 1968 till 2014) will be studied. To achieve the research objectives, a corpus-based research procedure was implemented, using ESLO Corpus “Enquête Sociolinguistique à Orléans”. It is divided into two sub-corpora ESLO 1 (collected between 1969 and 1974) and ESLO 2 (collected starting from 2014). Based on the findings, it comes clear that the young generation drops more frequently schwa in their spontaneous speech. Their rate of elision was higher in both corpora compared to the one of the old speakers (34,6%, for the old generation compared to 41,7% for the young one). Yet, it is found that the increase of schwa deletion through the diachronic period of forty years is not highly significant. However, it was found that schwa deletion is conditioned by other linguistic and sociolinguistic variables which have not been addressed in this research paper. Consequently, the discussion is left for future research.